RNA Polymerase Activity Associated with Bacteriophage ϕ6 Nucleocapsid - Partridge, James E.; Van Etten, James L.; Burbank, Dwight E.; Vidaver, Anne K. (Journal of General Virology, 1979)
SUMMARY The Pseudomonas phaseolicola bacteriophage ϕ6 nucleocapsid incorporated ATP, UTP, CTP and GTP into ssRNA products which sedimented at the same rate as heat-denatured small and medium dsRNA components. Hybridization of the separated ssRNA products with denatured dsRNA revealed that the small ssRNA hybridized only to small dsRNA and the medium ssRNA to the medium dsRNA. Synthesis of the large ssRNA was not observed. The RNA polymerase reaction proceeded through a replicative intermediate-like RNA probably via a semiconservative mechanism.